A survey of UK percutaneous lung biopsy practice: current practices in the era of early detection, oncogenetic profiling, and targeted treatments. Issue 9 (September 2018) - Tavare, A.N.; Hare, S.S.; Miller, F.N.A.; Hammond, C.J.; Edey, A.; Devaraj, A.
Abstract : Aim: To ascertain current percutaneous lung biopsy practices around the UK. Materials and methods: A web-based survey was sent to all British Society of Thoracic Imaging (BSTI) and British Society of Interventional Radiology (BSIR) members (May 2017) assessing all aspects of lung biopsy practice. Responses were collected anonymously. Results: Two hundred and thirty-nine completed responses were received (28.8% response rate). Of the respondents, 48.5% worked in a teaching hospital and 51.5% in a district general hospital, while 32.6% (78/239) were specialist thoracic radiologists, 29.2% (70/239) "general" radiologists with a thoracic subspecialty interest, and 28% (67/239) interventional radiologists. Of the respondents, 30.1% (72/239) did not require pre-biopsy lung function tests (PFTs); 45.6% (108/237) stopped aspirin before the procedure; 97.5% primarily use computed tomography (CT) guidance for biopsy and 88.7% (212/239) perform core needle biopsy (CNB); and 86.6% of radiologists use a co-axial technique. There was wide variation in the number of samples routinely taken with most radiologists performing 1–2 passes (55.9%) or 3–4 passes (40.8%). Sixty-four percent reported using chest drain prevention techniques to minimise the impact of iatrogenic pneumothorax, with needle aspiration most frequent (43.9%). Timing of post-biopsy chest radiography (CXR), performed by 95.8% (228/239), also varied greatly: most commonly at either 1 hour (23%), 2 hours (24.7%), or 4 hours (22.6%). Moreover, the time of patient discharge after uncomplicated biopsy was variable, although the majority (66.1%) discharge patients after ≥4 hours. Conclusion: There are striking variations among surveyed UK radiologists performing lung biopsy in decision-making, pre-biopsy work-up, post-biopsy monitoring, management of pneumothorax, and discharge. The results suggest a need for new updated national percutaneous lung biopsy guidelines. Highlights: Many aspects of lung biopsy practice vary across the UK. Post biopsy care, such as time of chest radiograph and duration of observation are particularly variable. Decision making and "willingness to biopsy" differ markedly between respondents. Most use coaxial technique and cutting/core needles, usually taking 1–4 samples. A number of chest drain prevention techniques are widely used.